Studi komparatif hukum fikih empat mazhab tentang thaharah dan kategori najis - Nasrulloh, Abdul Aziz (Maliki Interdisciplinary Journal, 2026)
This study provides a comprehensive comparative analysis of the jurisprudential rulings of the four major Islamic schools of thought Hanafiyah, Malikiyah, Shafi’iyah, and Hanabilah regarding purification (ṭahārah) and categories of impurity (najāsah). These issues are fundamental aspects that determine the validity of a Muslim’s acts of worship.The background of this research arises from the differing opinions among these schools, which often lead to confusion in daily religious practice. Therefore, a structured comparative understanding is needed. The urgency of this study lies in its aim to offer a clear mapping of the differences and common grounds in the laws of purification, thereby strengthening jurisprudential tolerance and facilitating ease in worship.The research employs a library research method with a comparative approach, analyzing primary sources such as classical fiqh texts as well as contemporary literature. Through this approach, the study examines the foundational considerations used by each school in formulating rulings on purification and impurity.The findings show that although there are variations in the determination of impurities, methods of purification, and standards of cleanliness for substances or water, all schools uphold the same fundamental principle of preserving the purity required for valid worship. This study demonstrates that the differences among the schools are ijtihād-based and provide legal flexibility in accordance with the contextual needs of the Muslim community.